Arabic text steganography using lunar and solar diacritics - Rawaa Hamza Ali; Ban Nadeem Dhannoon; Mohamed Iedan Hamel (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The need to hide essential information has rapidly increased as mobile devices and the internet has overgrown. Steganography is a method created to create hidden communication. Recently, methods have been developed to hide important information using text steganography. This work-study takes advantage of the possibility of concealing data in all diacritics after the two letters ال)) in the cover text. In the presented study, we propose a new algorithm in steganography in Arabic text as a cover text. After pre-processing the cover text, the algorithm hides the elements of secret messages inside the Arabic letters by adding appropriate diacritics (like Hamzah Al-Wasl) on the extracted words beginning with (ال) according to its third letter type (solar or lunar). In the proposed algorithm, the length of the secret message is determined so that the intended recipient can extract the hidden message accurately. The proposed algorithm is robust against the attack because the change in the cover text is small and imperceptible. On the other hand, since Arabic is used as a cover text, the breadth of the inclusion depends on the number of words beginning with (ال) definition.